Determinants and Trends of COVID-19 Vaccine Hesitancy and Vaccine Uptake in a National Cohort of US Adults: A Longitudinal Study. Issue 4 (5th January 2022) - Rane, Madhura S; Kochhar, Shivani; Poehlein, Emily; You, William; Robertson, McKaylee M; Zimba, Rebecca; Westmoreland, Drew A; Romo, Matthew L; Kulkarni, Sarah G; Chang, Mindy; Berry, Amanda; Parcesepe, Angela M; et al.
Abstract: We estimated the trends and correlates of vaccine hesitancy and its association with subsequent vaccine uptake among 5, 458 adults in the United States. Participants belonged to the Communities, Households, and SARS-CoV-2 Epidemiology COVID (CHASING COVID) Cohort, a national longitudinal study. Trends and correlates of vaccine hesitancy were examined longitudinally in 8 interview rounds from October 2020 to July 2021. We also estimated the association between willingness to vaccinate and subsequent vaccine uptake through July 2021. Vaccine delay and refusal decreased from 51% and 8% in October 2020 to 8% and 6% in July 2021, respectively. Compared with non-Hispanic (NH) White participants, NH Black and Hispanic participants had higher adjusted odds ratios (aOR) for both vaccine delay (for NH Black, aOR = 2.0 (95% confidence interval (CI): 1.5, 2.7), and for Hispanic, 1.3 (95% CI: 1.0, 1.7)) and vaccine refusal (for NH Black, aOR = 2.5 (95% CI: 1.8, 3.6), and for Hispanic, 1.4 (95% CI: 1.0, 2.0)) in June 2021. COVID-19 vaccine hesitancy, compared with vaccine-willingness, was associated with lower odds of subsequent vaccine uptake (for vaccine delayers, aOR = 0.15, 95% CI: 0.13, 0.18; for vaccine refusers, aOR = 0.02; 95% CI: 0.01, 0.03 ), adjusted for sociodemographic factors and COVID-19 history. Vaccination awareness and distribution efforts should focus on vaccine delayers.